The Potential Therapeutic Role of Celastrol in Patients With Heart Failure With Preserved Ejection Fraction - Maryam Ajmal; Aisha Ajmal; Lei Huang; Lei Huang; Lingfang Zeng (Frontiers in Cardiovascular Medicine, 2021)
Analysis of left ventricular systolic dysfunction remained at the centre of heart failure research for many years (also known as heart failure with reduced ejection fraction, HFrEF). Although more than 50% of all heart failure patients experience a form of heart failure characterised by preserved ejection fraction (HFpEF), the pathophysiological mechanisms leading to this form of heart failure remain not well-understood. Several evidence-based treatments for HFrEF are in routine use, but there are limited evidence-based therapies for HFpEF. The effects of these remain controversial, with current treatment options being limited to managing the associated symptoms and conditions. Accumulating evidence demonstrates that pro-inflammatory and oxidative stress pathways play key roles in the development and progression of HFpEF, such as the Unfolded Protein Response (UPR) and inducible nitric oxide synthase. Celastrol, derived from medicinal plants, is a bioactive compound with strong anti-inflammatory properties, which could deem it as fruitful in overcoming the effects of such dysregulated UPR. This literature review therefore focuses on Celastrol's anti-inflammatory and antioxidant activities, alongside its other potential therapeutic activities, and its ability to impede the pathways that are thought to be involved in the development of HFpEF, such as the JAK2/STAT pathway, to elucidate the potential therapeutic role of this bioactive compound, in the treatment of HFpEF.